Un’educazione oltre le differenze: un’analisi delle normative europee e italiane per l’inclusione interculturale degli studenti migranti nelle scuole = Education beyond differences: an analysis of European and Italian regulations for the intercultural inclusion of migrant students in schools - Patera, Salvatore (Revista Educação Por Escrito)
The research aims at analysing in a comparative way, the main documents produced on the topic of entry, integration and inclusion of students with a migrant background by major international and national organisations dealing with education and training. Through the analysis of selected documents, the research intends to retread the evolution of the processes of entry, integration and inclusion over the last 40 years, taking their social significance and their reception in the school context. The main objective will be to understand how these organisations and the Italian educational system deal with the issue of inclusion of foreign students, from the point of view of the strategies and policies proposed in order to promote increasingly inclusive educational systems. The research will analyse the impacts that these documents have had on the regulatory and institutional level and on school practices, in order to highlight the possibilities of implementing policies aimed at improving the inclusion of migrant students. Furthermore, a review of the terminological evolution in use in the documents and its impact on European education systems, will allow for a better understanding of the linguistic dynamics underlying policy-making processes